RAISE model: Teaching expressive, critical, and polite speaking skills in elementary school students - Muchamad Fauyan; Anwar Efendi; Sugeng Bayu Wahyono (Directorate of Research and Community ServiceUniversitas Negeri Yogyakarta, 2026)
This study seeks to develop and rigorously evaluate the effectiveness of the RAISE (Recognising, Analysing, Integrating, Speaking, and Evaluating) model in enhancing expressive, critical, and respectful speaking skills amongst fifth-grade primary school students. Employing a Research and Development (R&D) methodology grounded in the Dick and Carey instructional design framework, the research involved a cohort of 202 students across five schools in Pekalongan City. Data were systematically gathered utilising questionnaires, observations, interviews, rating scales, and speaking tests. Subsequently, these data were analysed employing a mixed-methods approach, comprising quantitative measures (paired t-tests, ANCOVA, N-gain, and effect size calculations) alongside qualitative descriptive analysis. The empirical trials demonstrated the model’s robust feasibility and practicality, revealing statistically significant improvements in both linguistic (pronunciation, vocabulary, and syntactic structure) and non-linguistic domains (fluency, confidence, content mastery, and ethical communication). Ultimately, this research presents a novel, evidence-based pedagogical framework that integrates jurisprudential inquiry, multimodal literacy, and ethical communication, thereby addressing critical deficiencies in primary speaking education. The RAISE model provides a highly transferable approach to cultivating 21st-century competencies and holistic communication proficiency within diverse educational contexts.